Shabada sañcāra : gurabāṇī adhiaina de paripekha wica - Ammritapāla Kaura (Ammritasara : Rawī Sāhita Prakāshana, 2003)
Articles on Sikh religious literature.
In Panjabi.
Includes bibliographical references (p. 197-200).
Keywords: Sikh literature -- History and criticism